Стратегічні напрями розвитку Науково-технічної бібліотеки Національного університету харчових технологій в умовах інформаційного впливу - Левченко, Наталія Петрівна (My University, 2017)
У статті представлено стратегію розвитку НТБ НУХТ, яка передбачає впровадження інноваційних підходів і методів для потреб навчального процесу, наукових досліджень. У рамках цієї стратегії бібліотека повинна трансформуватися в ресурсний інформаційно-аналітичний центр університету. Розкриваються деякі подробиці такого розвитку на прикладі двох пілотних проектів. The article presents the strategic directions, mechanisms, processes within the framework of the implementation of the “Concept of the development of the scientific and technical library of the National University of Food Technologies forthe period 2017-2020.” The purpose of the article is to study the current state of the library and determine the priority tasks of the library in the conditions of information influence and qualitative changes of the external and educational environment. The modern model of the library, in which separate projects operate, reflect the activity of the library as a resource information and analytical center. The result of design works is considered. The results of research and work in implementing the adopted development strategy provide the opportunity to turn the library into a center of education that not only supports the information activities of the university, but directly participates in the educational process.
Keywords: наукова бібліотека; стратегічний розвиток; модель розвитку; інформаційний центр; scientific library; strategic development; model of development; information center